Politik Kewarganegaraan dan Defisit Keterwakilan Perempuan Pengawas Pemilu di Provinsi Riau - Ricky Santoso Muharam; Sudaryatie Sudaryatie (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Y, 2026)
This article examines women's representation in the membership of the Election Supervisory Agency (Bawaslu) at the district and municipal level in Riau Province for the 2023–2028 term, using the frameworks of citizenship politics and women's political representation. Indonesian Law No. 7 of 2017 mandates that the composition of election management bodies observe a minimum of 30 per cent women's representation, yet the statutory verb